Business statistics communicating with numbers - Jaggia, Sanjiv; Hawke, Alison Kelly (McGraw-Hill/Irwin, 2013)
Suitable for students studying Business Statistics, this title presents the material in an accessible way by using timely business applications to which students can relate.